Synergistic effect on lignolytic enzyme production through co-culturing of white rot fungi during solid state fermentation of agricultural residues - Jatinder Singh; Anjali Mandal; Yogalakshmi Kadapakkam Nandabalan (Bulletin of the National Research Centre)
Abstract Background The current study has demonstrated that the co-culturing strategy as compared to mono-culture enhanced the lignolytic enzymes activity due to their synergistic effect on solid substrate. Synergistic effect during the co-culturing of white rot fungi (WRF) can be utilised to degrade contaminants from the environment since lignolytic enzymes are responsible for the degradation of lignin and organic pollutants. Methods This study used a mixed WRF culture comprising Pleurotus ostreatus (PO), Trametes versicolor (TV), Phanerochaete chrysosporium (PC) and Daedaelia flavida (DF) to produce enzymes such as laccase, manganese (MnP) and lignin peroxodase (LiP) using solid state fermentation (SSF) process. Wheat straw (WS), paddy straw (PS) and cotton stalks (CS) were selected as substrates for lignolytic enzyme production to lower the cost and length of the process. Based on their enzymatic activity, selected fungal strains were categorised. Results Pair of TV-PC on reactive blue MR (RB-MR) dye agar plates exhibited the highest levels of peroxidase activity, with a maximum diameter of 45 mm. TV and PC pair showed the highest levels of laccase (810 U/L), LiP (693 U/L) and MnP (681 U/L) activity due to synergistic interaction and CS substrate was verified to be beneficial for laccase, MnP and LiP enzyme production. SDS-PAGE and SEM analysis characterised the lignolytic enzymes and cotton stalks substrate, respectively. Conclusions In the present investigation, Trametes versicolor and Phanerochaete chrysosporium showed the highest laccase and peroxidases activity, respectively. Synergistic effect was observed during co-culturing of Trametes versicolor and Phanerochaete chrysosporium on RB-MR dye. Significantly, the highest lignolytic activity was observed in cotton stalk substrate.